French sociology - Heilbron, Johan (Cornell University Press, 2015)
French Sociology offers a uniquely comprehensive view of the oldest and still one of the most vibrant national traditions in sociology. Johan Heilbron covers the development of sociology in France from its beginnings in the early nineteenth century through the discipline's expansion in the late twentieth century, tracing the careers of figures from Auguste Comte to Pierre Bourdieu. Presenting fresh interpretations of how renowned thinkers such Émile Durkheim and his collaborators defined the contours and content of the discipline and contributed to intellectual renewals in a wide range of other human sciences, Heilbron's sophisticated book is both an innovative sociological study and a major reference work in the history of the social sciences. Heilbron recounts the halting process by which sociology evolved from a new and improbable science into a legitimate academic discipline. Having entered the academic field at the end of the nineteenth century, sociology developed along two separate tracks: one in the Faculty of Letters, engendering an enduring dependence on philosophy and the humanities, the other in research institutes outside the university, in which sociology evolved within and across more specialized research areas. Distinguishing different dynamics and various cycles of change, Heilbron portrays the ways in which individuals and groups maneuvered within this changing structure, seizing opportunities as they arose. French Sociology vividly depicts the promises and pitfalls of a discipline that up to this day remains one of the most interdisciplinary endeavors among the human sciences in France. -- from back cover.